Assessing the role of food MSMEs in providing employment for women and youth in Ethiopia - Mekonnen, Daniel Ayalew; de Brauw, Alan (International Food Policy Research Institute, 2024)
This paper analyzes the employment characteristics of food micro-, small-, and medium-sized enterprises (MSMEs), using survey data collected from 1,686 food vendors in Addis Ababa and Butajira, Ethiopia. The data suggest that 74 percent of the enterprises were formal or had a tax identification number. The average number of workers across enterprises was 2.3, which varies between 1.2 as in the case of street sellers and 5.3 as in the case of restaurants. Among enterprises with an additional worker besides the owner, only about 32 percent of them had part-time workers. The share of youth in part-time and full-time employment was 43 percent and 28 percent, respectively. Adults especially women constituted the majority of both full-time and part-time workers. More than 53 percent of the enterprises were owned and operated by women, but the significant majority of them were one-person enterprises, suggesting that women-owned enterprises are less likely to create additional jobs. In fact, results from the logistic regressions suggest that the odds of women-owned enterprises employing anyone were between 0.53 to 0.62 times the odds of men-owned enterprises. Only 17 percent of the enterprises had outstanding loans at the time of the survey. However, the relationship between loan uptake status and the number of workers was not strong. Results also indicate that the number of workers was positively and significantly associated with the size of enterprise revenue but the relationship with profitability was not strong, possibly because the size of profits per worker was quite low. To put this in perspective, the size of profits per worker (for example, for street sellers who are mostly self-employed and rarely take their wages into account during cost calculations) was less than the cost of a healthy diet. Overall, while the food MSMEs in the study sites may have the potential to deliver food at lower cost and contribute to gender and social inclusion through self-employment, the scope of food MSMEs, especially those run by women, to generate additional employment appears to be limited.